Socio-Political Telegram Channels Reporter and Lentach as New Media - Valentin E. Solomin; Nikita A. Karev (Виртуальная коммуникация и социальные сети)
The article describes new digital mass media that engage users in content creation and distribution. The research covered the content published in Telegram channels Reporter and Lentach between November 29 and December 12, 2021. The analysis revealed such properties of new media as interactivity, hypertextuality, convergence, digital content, and media environment. The channels use the Telegram platform to interact with readers. They cover the entire range of socially significant topics in typical journalistic genres. However, Reporter specializes in a qualitative analysis of socially significant topics, while Lentach reflects the event agenda in an ironic and sarcastic manner. The research prospects have two main tasks: 1) to identify the optimal forms of formation and promotion of content for messengers and social networks; 2) to develop models of interaction with the audience. The results of the study can be applied by media community workers, media analysts, and new media researchers.